Mood Chem: Development of an Android-Based STPM Chemistry Learning Application using Gamification Approach - YEOH, PEI SHAN; Ismail, Mohd Norasri (Applied Information Technology And Computer Science, 2023)
Organic chemistry is an important topic in the STPM Chemistry curriculum. Many students struggle with it as it requires extensive memorization of numerous reactions. Most Organic Chemistry learning applications found in Google Play did not specify the target user, and the topics were not based on the Malaysian Examination Council (MEC) STPM Chemistry syllabus. Thus, Mood Chem has been developed as a learning tool for STPM science students to learn Organic Chemistry through a gamification approach. It is an Android application with syllabus-based content. The objectives of this project are to design a mobile learning application about Organic Chemistry for STPM students based on the Malaysian Examination Council (MEC) STPM Chemistry syllabus, to develop a mobile learning application about Organic Chemistry on the Android-based mobile platform with a gamification approach and to test the functionality and user acceptance of the mobile learning application about Organic Chemistry to STPM students. This project is being developed using the Agile model. It was tested on 30 STPM science stream students. In the beta testing of Mood Chem, more than 50% of the respondents strongly agreed or agreed with the statement in all constructs. As a result, Mood Chem can help students understand Organic Chemistry and is well received by the intended audience.